Penerapan Standard Operating Procedures Bagian Kitchen Di Hotel the Haven Suites Bali Berawa - Yasa, A.A Kompiang Agus Nuarta; Lestari, Denok; Sudiarta, I Nyoman (Jurnal Studi Perhotelan dan Pariwisata, 2024)
Purpose: The purpose of this study is to find out the application of SOP in the kitchen section and find out what are the obstacles in implementing SOP at The Haven Suites Bali Berawa. Research methodology: The data collection methods used are observation, interviews and documentation.Results: Based on the results of this study, it shows that the application of SOP in the kitchen has been carried out quite well but not implemented as a whole so that the SOP are not applied optimally. Conclusions: Based on the results of qualitative research conducted through interview, observation, and documentation techniques, it can be concluded that the implementation of Standard Operating Procedures (SOP) in the kitchen section of The Haven Suites Bali Berawa has generally been implemented well. However, there are still some SOPs that have not been implemented optimally. The main obstacles faced in the implementation of SOPs include the lack of kitchen staff due to labor reduction during the pandemic and the low discipline of trainee staff in implementing SOPs, which is caused by the absence of a clear reward and punishment system.Limitations: This study has limitations in terms of scope, which is only focused on one operational section, namely the kitchen, and was conducted in one hotel only, so the results may not necessarily be generalized to other hotels. In addition, the limited research time and post-pandemic operational conditions also affect the completeness of data and direct observation.Contribution: This research is expected to contribute to hotel management in evaluating and improving the implementation of SOPs in the kitchen, especially in terms of adding staff and implementing a reward and punishment system for trainees. In addition, the results of this study can also be an academic reference in the development of operational management studies in the hospitality industry.Keywords: Application, Kitchen, Standard Operating Procedures, How to Cite: Yasa, A, A, K, A, N. Lestari, D. Sudiarta, I, N. (2024). Penerapan Standard Operating Procedures Bagian Kitchen Di Hotel the Haven Suites Bali Berawa. Jurnal Studi Perhotelan dan Pariwisata, 2(2), 99-105.